Allusion in Novel "24 Jam Bersama Gaspar Sebuah Cerita Detektif" by Sabda Armandio Semantic Approach - Meyra, Kiki Ayu; Rahmat, Wahyudi; Putri, Febrina Riska (Jurnal Curricula, 2018)
Allusion is a form of language that has a negative relationship and it becomes something that is very disliked by many people. Even that is the background of this research, that people only think that what is in a literary work always reveals the positive values contained in ad work, but often forgets something  that smeels negative. This study  reveals the form onf syndicated language used by characters in the novel 24 Jam Bersama Gaspar Sebuah Cerita Detektif by Sabda Armandio. The study use Keraf theory (2010) as form, Manaf and Aminuddin as forming meaning. The method  suggested by Sudaryanto (1993). The result of this study  is some indicate that the most language style found in the novel 24 Jam Bersama Gaspar Sebuah Cerita Detektif by Sabda Armandio is sarcasm and irony. The  form of the language of satire contains bitterness, blemish, hurt and is less pleasent to hear.